Problems of Combining Absolute and Relative Points and Area Symbols, With Special Reference to Mapping Industrial Workers in North and West Sumatera, Indonesia - T. Lukman Aziz (Journal of Mathematical and Fundamental Sciences, 1985)
Abstract. The most important phase of cartographic processes is the selection of map symbols for data presentations, since the effectiveness of maps as a medium of communication depends on this selection. A great variety of map symbols can be chosen. This study shows how to utilize symbols in solving a typical problem of a map showing distribution.Sari. Salah satu tahap yang paling menentukan dalam proses kartografi adalah pemilihan simbol untuk memetakan data. Hal ini disebabkan oleh kenyataan bahwa symbol itu banyak sekali macamnya. Manfaat peta sebagai media komunikasi akan sangat terasa bila symbol yang dipilih tepat atau cocok dengan maksud serta tujuan pembuatan peta tadi. Tulisan ini membahas bagaimana cara memilih serta menggunakan symbol untuk suatu persoalan, khususnya yang menyangkut masalah distribusi.